Contracting and Safety Exploring Outsourcing Practices in High-Hazard Industries - Hayes, Jan; Tillement, Stéphanie (SpringerBriefs in Applied Sciences and Technology; SpringerBriefs in Safety Management, 2022)
This open access book examines the increase in outsourcing, contracting and subcontracting as ways of organising work. It explores the impact of these employment arrangements on public safety, particularly when they are linked to complex supply networks in a range of engineering industries including oil and gas, nuclear power and aviation. The brief provides practical recommendations on how best to manage arrangements that target short-term profitability and also maintain excellence in long-term safety outcomes. The brief is a source of advice for organisations on how to maximise the benefits and minimise long-term system reliability issues that can be introduced by contracting and outsourcing, rather than assuming it to be a wholly negative or positive practice. Contracting and Safety comprises qualitative, empirical studies focusing on high-reliability organisation. As such, this brief provides a rich picture of the experience of working in complex supply chains. It will be of interest to researchers in industrial safety, as well as safety professionals and project managers within engineering industries.